Identification of the promoter region of human interleukin 1 type I receptor gene: multiple initiation sites, high G+C content, and constitutive expression. - Ye, K (1993)
To better understand the role of interleukin 1 (IL-1) and its receptor in disease, we have isolated a genomic clone of the human IL-1 type I receptor and have identified the promoter region. There are multiple transcriptional initiation sites as demonstrated by primer extension. DNA sequence analysis shows that the promoter region contains neither a TATA nor a CAAT box; however, the 5' upstream regulatory elements contain two AP-1-like binding sites. The internal regulatory sequences found immediately downstream to the 5' transcriptional start site contain four Sp1 binding domains and have a high G+C content of 75%. This portion of the 5' untranslated region of the mRNA can form stable secondary structure as predicted by computer modeling. Base pairs -4 to + 10 share striking resemblance to an initiator sequence that directs basal expression of certain TATA-less genes-e.g., terminal deoxynucleotidyltransferase in lymphocytes. The IL-1 receptor promoter directs basal expression of chloramphenicol acetyltransferase in transiently transfected cells. Overall, the promoter of the IL-1 type I receptor gene resembles that of constitutively expressed genes that have housekeeping- and/or growth-related functions. The constitutive nature of the promoter may account for this gene being expressed at low levels in diverse cell types. Our finding sheds more understanding into the mechanisms governing the regulation of the IL-1 receptor in health and disease.